Methanogens and Methanotrophs Show Nutrient-Dependent Community Assemblage Patterns Across Tropical Peatlands of the Pastaza-Marañón Basin, Peruvian Amazonia - Finn, Damien Robert; Ziv-El, Michal; van Haren, Joost; Park, Jin Gyoon; del Aguila-Pasquel, Jhon; Urquiza–Muñoz, Jose David; Cadillo-Quiroz, Hinsby (Frontiers in Microbiology, 2020)
Tropical peatlands are globally important carbon reservoirs that play a crucial role in fluxes of atmospheric greenhouse gases. Amazon peatlands are expected to be large source of atmospheric methane (CH4) emissions, however little is understood about the rates of CH4 flux or the microorganisms that mediate it in these environments. Here we studied a mineral nutrient gradient across peatlands in the Pastaza-Marañón Basin, the largest tropical peatland in South America, to describe CH4 fluxes and environmental factors that regulate species assemblages of methanogenic and methanotrophic microorganisms. Peatlands were grouped as minerotrophic, mixed and ombrotrophic categories by their general water source leading to different mineral nutrient content (rich, mixed and poor) quantified by trace elements abundance. Microbial communities clustered dependent on nutrient content (ANOSIM p < 0.001). Higher CH4 flux was associated with minerotrophic communities compared to the other categories. The most dominant methanogens and methanotrophs were represented by Methanobacteriaceae, and Methylocystaceae, respectively. Weighted network analysis demonstrated tight clustering of most methanogen families with minerotrophic-associated microbial families. Populations of Methylocystaceae were present across all peatlands. Null model testing for species assemblage patterns and species rank distributions confirmed non-random aggregations of Methylococcacae methanotroph and methanogen families (p < 0.05). We conclude that in studied amazon peatlands increasing mineral nutrient content provides favorable habitats for Methanobacteriaceae, while Methylocystaceae populations seem to broadly distribute independent of nutrient content.